Layerwise Equilibrium Theory: A Critical Analysis of Single Layer Models - Thokal, R T; Gupta, S K; Chauhan, H S (Annals of Arid Zone, 2016)
An analytical solution for predicting leaching of salts is presented. In deriving this equation. soil profile is assumed to consist of a single layer, while total amount of water is assumed to have been applied in finite splits which are referred to as number of pulses. The proposed solutions are compared with existing models which are either based on single pulse-multilayer concept or infinite pulses-single layer concept. It is shown that predictions from such models, including those from the proposed models, are within a close range. For example. when salts are distributed uniformly in the soil profile initially, predicted leaching after drainage of I PY from various models is around 60% (60.6 to 63.2%), while it is 37% (36.8 to 38.6%) if salts are assumed to be concentrated in the surface layer. As field and laboratory experimental data show wide variation in leaching after drainage of' I PY, such models will fail to describe many field situations. Therefore, it is proposed that. to simulate the solute transport more realistically, both soil and water should be subdivided into number of layers and number of pulses, respectively. With this modification, the results from leaching of uniformly distributed salts indicate that calculated leaching after passing one pore volume could range from 60% to more than 80% (pulse = 10, number of layers = 10), which is common range reported in the field experiments. Thus, in computer simulations, such an approach would provide flexibility in assessing solute transport more realistically.